A Populist Foreign Policy? The Impact of the Trump Presidency on the Transatlantic Relation. (January 2022) - Bustinduy, Pablo
In recent years, a considerable attention has been paid to changes introduced by the Trump administration in the general orientation of the US foreign policy. Using the transatlantic relation as a prism for analysis, this article assesses different interpretations of rupture and continuity in Trump's foreign policy. It does so by distinguishing two main theories of populism, as a political style and as a political logic, from which derive very different implications for the analysis of Trump's foreign policy legacy, the future of the transatlantic relation and the plausibility of a 'return to normalcy' at a time of deep crisis of globalization.